Porcine model for the study of sperm capacitation, fertilization and male fertility - Zigo, Michal; Maňásková-Postlerová, Pavla; Zuidema, Dalen; Kerns, Karl; Jonáková, Věra; Tůmová, Lucie; Bubeníčková, Filipa; Sutovsky, Peter (Cell and tissue research, 2020)
Mammalian fertilization remains a poorly understood event with the vast majority of studies done in the mouse model. The purpose of this review is to revise the current knowledge about semen deposition, sperm transport, sperm capacitation, gamete interactions and early embryonic development with a focus on the porcine model as a relevant, alternative model organism to humans. The review provides a thorough overview of post-ejaculation events inside the sow's reproductive tract including comparisons with humans and implications for human fertilization and assisted reproductive therapy (ART). Porcine methodology for sperm handling, preservation, in vitro capacitation, oocyte in vitro maturation, in vitro fertilization and intra-cytoplasmic sperm injection that are routinely used in pig research laboratories can be successfully translated into ART to treat human infertility. Last, but not least, new knowledge about mitochondrial inheritance in the pig can provide an insight into human mitochondrial diseases and new knowledge on polyspermy defense mechanisms could contribute to the development of new male contraceptives.
Keywords: fertilizace; fertilita; Zona pellucida; Sperm Capacitation; Disease Models, Animal; Capacitation; mužské pohlaví; Fertilization; Swine; Animals; modely nemocí na zvířatech; zvířata; kapacitace spermií; Humans; Fertility; Male fertility; prasata; lidé; Male; Pig